Fasihuddin Ashraf’s Literary Column In Light of the Special Study of "Khama Ba Josh" - Ishaq, Muhammad; Ali, Muhammad Said; Khalil, Sadia (sourcecoder, 2022)
Literary column writing has now been incorporated into university curricula, recognizing its significance and relevance in the field of prose literature. Dr. Faseeh-ud-Din Ashraf stands as a prominent literary column writer, whose creative talents extend into this genre. A distinguished police officer, he has authored numerous books in English, Urdu, and Pashto, covering both poetry and prose. Literary column writing serves as a vital avenue for the expression of his creative abilities, with several collections published. This article undertakes an appraisal of the fundamental attributes of Dr. Faseeh-ud-Din Ashraf’s literary column writing, highlighting his distinct qualities as a commentator. The piece delves into aspects such as literary commentary, meaningful utilization of poetry, literary camaraderie, sketching, and stylistic elements to outline the unique facets of Dr. Faseeh-ud-Din Ashraf’s column writing.